Use of mechanical and noninvasive ventilation in black and white chronic obstructive pulmonary disease patients within the Veterans Administration health care system - Cannon, Katrina T; Sarrazin, Mary Vaughan; Rosenthal, Gary E; Curtis, Ann E; Thomas, Karl W; Kaldjian, Lauris C (Medical care, 2009)
Black patients are more likely than white patients to prefer and receive more life-sustaining interventions in advanced stages of disease. However, little is known about potential racial differences in use of mechanical ventilation (MV), and the newer modality of noninvasive ventilation (NIV), in treatment of chronic obstructive pulmonary disease (COPD). To determine if rates of MV and NIV use differ among black and white patients admitted to Veterans Administration (VA) hospitals for COPD exacerbation. Retrospective cohort analysis of VA database FY2003 to FY2005 including 153 hospitals nationwide. All black (n = 479) and white (n = 31,537) patients admitted with COPD exacerbation. Ventilation use during hospitalization as identified by ICD-9-CM codes for MV and NIV. Hierarchical logistic regression compared rates of MV or NIV use among black and white patients, adjusting for patient characteristics and accounting for hospital-level variation. Unadjusted rates of MV were higher in black patients than in white patients (4.1% vs. 3.0%; P < 0.001), but similar for NIV (6.0% vs. 6.1%; P = 0.65). The adjusted odds of MV for black patients relative to white patients remained higher (OR = 1.27, 95% CI: 1.01-1.54; P < 0.01) while the adjusted odds of NIV remained similar (OR = 0.94, 95% CI: 0.82-1.08; P = 0.38). Black patients with COPD exacerbation in VA hospitals are more likely than white patients to receive MV, and this difference is not explained by available clinical or demographic variables. By contrast, black and white patients are equally likely to receive NIV. These findings suggest that unmeasured factors, such as patient preferences or disease severity, may be affecting the use of MV in this setting and therefore warrant further investigation.